(untitled) (Annals of Medical Research, 2023)
Aim: Adolescent pregnancies constitute a very important health issue for maternal and fetal with social and economic consequences. The purpose of this study is to analyze the perinatal outcomes of adolescent pregnancies in a training and research hospital. Materials and Methods: Perinatal outcomes for adolescents between the ages of 10 and 19 years old and adults between the ages of 20 and 30 years old between 2015 and 2019 were evaluated and compared retrospectively, using an obstetric and neonatal database from Van Training and Research Hospital. Results: Cesarean section (CS) rates were 19,4 % vs. 30% in the adolescent and control groups, respectively (p<0.05). The rates of preterm delivery (PD), premature rupture of membranes (PROM), preeclampsia, and eclampsia were significantly higher among adolescents (p<0.05). After adjusting for maternal age, gravida, parity, hemoglobin level, education, socioeconomic status, and pregnancy follow-up, the rates of NVD (aOR 2.004, 95% CI 1.739-2.309), PB (aOR 1.419, 95% CI 1.122-1.794), PROM (aOR 4.401, 95% CI 3.066-6.319) and low birth weight (<2,500 g; aOR 2.480, 95% CI 1.442-4.264) were elevated in the adolescent group. Conclusion: Adolescent pregnancy is associated with increased risk of PD, low birth weight, PROM, fetal mortality, and preeclampsia in our study. In this study, which evaluated adolescent pregnancies, maternal and fetal outcomes, risk of preeclampsia increased among maternal outcomes, and it was found to be associated with preterm birth, low birth weight, premature rupture of the membrane and increased fetal mortality from fetal outcomes. However, there are different results between studies because there are many factors affecting the results. More studies are needed to confirm these results. There is a need for more studies on adolescent pregnancies with important maternal and fetal outcomes not only for our country but also for many countries.